2009
DOI: 10.2116/analsci.25.1125
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Trace Polycyclic and Nitro Musks in Water Samples Using Optimized Solid-Phase Extraction by Gas Chromatography and Mass Spectrometry

Abstract: This study intended to develop a robust and sensitive method for simultaneous determination of polycyclic musks (HHCB and AHTN) and nitro musks (musk xylene (MX) and musk ketone (MK)) in water samples using optimized solid-phase extraction (SPE) by gas chromatography and mass spectrometry (GC-MS). The SPE procedure was optimized in terms of selections of SPE cartridge, sample pH, elution process, etc. The method detection limits (MDLs) were from 0.09 to 0.18 ng L -1 for the analytes. The recoveries ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…[20,21] Indeed, it has been reported that two nitromusks (MX and MK) and two polycyclic musks (HHCB and AHTN) accounted for 95% of the musks used in perfume market, [15] therefore, these nitromusks are still detected in environmental samples and in humans. [15,16,[22][23][24] In this study, MK was detected at the LOD-172.7 µg/kg dw in all of the WWTPs except for XT, while MX was found at the LOD-65.8 µg/kg dw in all of the WWTPs except for SGSC. MA was only detected in one sample (KFQD) at the LOD level.…”
Section: Levels and Source Of Synthetic Musks In Sludge Samplessupporting
confidence: 47%
“…[20,21] Indeed, it has been reported that two nitromusks (MX and MK) and two polycyclic musks (HHCB and AHTN) accounted for 95% of the musks used in perfume market, [15] therefore, these nitromusks are still detected in environmental samples and in humans. [15,16,[22][23][24] In this study, MK was detected at the LOD-172.7 µg/kg dw in all of the WWTPs except for XT, while MX was found at the LOD-65.8 µg/kg dw in all of the WWTPs except for SGSC. MA was only detected in one sample (KFQD) at the LOD level.…”
Section: Levels and Source Of Synthetic Musks In Sludge Samplessupporting
confidence: 47%
“…For this reason, some of them, namely polycyclic musks, are not completely removed during wastewater treatment (Lv et al, 2010;Posada-Ureta et al, 2012;Zeng et al, 2005;Zhang et al, 2008) and are therefore frequently found in surface waters (e.g. Lv et al, 2009;Posada-Ureta et al, 2012;Yang and Ding, 2012). In fact, the application of sludge and/or biosolids to agricultural fields is a direct input of musks into the soil (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As it was described for UV filters, traditional LLE [39] and SPE [50,84,90,99,101] have been used for the enrichment of musk fragrances. Non-polar sorbents like C18 [90] or PS-DVB [50] have been used.…”
Section: Musk Fragrancesmentioning
confidence: 99%
“…As it was described for UV filters, traditional LLE [39] and SPE [50,84,90,99,101] have been used for the enrichment of musk fragrances. Non-polar sorbents like C18 [90] or PS-DVB [50] have been used. However, Osemwengie and Steinberg [84] found that PMA-DVB with polar and non-polar properties showed better performance than the non-polar PS-DVB for on-site SPE extraction of different nitro and polycyclic musks.…”
Section: Musk Fragrancesmentioning
confidence: 99%